No association of PTPN22 gene polymorphism with rheumatoid arthritis in Turkey - GÜNDÜZ, FEYZA; DİRESKENELİ, RAFİ HANER (SPRINGER HEIDELBERG, 2009)
Although the association of rheumatoid arthritis (RA) with HLA-DRB1 (shared epitope) is well demonstrated in many ethnic populations, the role of other RA-associated risk loci is not clarified. In this study, the functional single nucleotide polymorphism (SNP) of PTPN22 gene was investigated in Turkey. 167 patients with RA and 177 healthy controls are genotyped by polymerase chain reaction (PCR)-RFLP for the SNP (rs2476601, A/G) of PTPN22 gene. Polymorphic region was amplified by PCR and digested with Xcm I enzyme. Heterozygous genotype (AG) was present in 5.1% (9/177) of the controls and in 6.6% (11/167) of RA group (p = 0.55, OR 1.3, 95% CI 0.53-3.26). There was also no association between any clinical feature, RF positivity and presence of this SNP. In conclusion, the distribution of PTPN22 polymorphism did not reveal any association with RA in Turkey.
Keywords: Rheumatoid arthritis; Single nucleotide polymorphism; PTPN22; SINGLE-NUCLEOTIDE POLYMORPHISM; TYROSINE-PHOSPHATASE; AUTOIMMUNE-DISEASES